Discovery of potent tubulin inhibitors targeting the colchicine binding site via structure-based lead optimization and antitumor evaluation - Wei Liu; Youyou He; Zhongjie Guo; Miaomiao Wang; Xiaodong Han; Hairui Jia; Jin He; Shanshan Miao; Shengzheng Wang (Taylor & Francis Group, 2023)
The colchicine binding site of tubulin is a promising target for discovering novel antitumour agents. Previously, we identified 2-aryl-4-amide-quinoline derivatives displayed moderate tubulin polymerisation inhibitory activity and broad-spectrum in vitro antitumour activity. In this study, structure based rational design and systematic structural optimisation were performed to obtain analogues C1∼J2 bearing diverse substituents and scaffolds. Among them, analogue G13 bearing a hydroxymethyl group displayed good tubulin polymerisation inhibitory activity (IC50  =  13.5 μM) and potent antiproliferative activity (IC50 values: 0.65 μM∼0.90 μM). G13 potently inhibited the migration and invasion of MDA-MB-231 cells, and displayed potent antiangiogenic activity. It efficiently increased intracellular ROS level and decreased MMP in cancer cells, and obviously induced the fragmentation and disassembly of the microtubules network. More importantly, G13 exhibited good in vivo antitumour efficacy in MDA-MB-231 xenograft model (TGI  =  38.2%; i.p., 30 mg/kg).